Analisis Pemberdayaan Sumber Daya Manusia Dan Lingkungan Kerja Terhadap Kinerja Karyawan Klinik Indai Bunda - Johansyah, Ahmad; Josiah , Trisnowati (Jurnal Multidisiplin, 2025)
Organizational goals can be achieved through the positive performance of its members. Empowering human resources begins with investing in developing employee skills and knowledge. The company provides various training and education programs that are relevant to the industry and accommodate individual needs to develop professionally. Apart from empowering human resources, work environment factors can also influence employee performance in an agency. This research aims to determine the effect of empowering human resources and the work environment on employee performance at the Indai Bunda Clinic in 2024.The type of research used in this research is quantitative field research, namely research that emphasizes analysis of data in the form of numbers and the research examines real life in the field, in this case the object being studied. This research used 33 research respondents.Based on data analysis, a hypothetical answer has been found, namely as follows; There is an influence of human resource empowerment (X1) on employee performance (Y), with an influence level of 24.8%. There is an influence of the work environment (X2) on employee performance (Y) with an influence level of 31.8%. There is an influence of human resource empowerment (X1) and work environment (X2) together on employee performance (Y) with an influence level of 44.4%.